2009
DOI: 10.1111/j.1473-6861.2008.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Socialization of student nurses – the role of the mentor

Abstract: In this paper, the role of the mentor in supporting student learning and development in clinical practice areas and promoting their socialization into their occupational roles is discussed and explored. Examining the literature relating to the mentor, the essential nature of this role is investigated and related to the socialization process of student nurses; with the importance of maintaining and developing an effective learning environment for the students being examined and considered. The paper concludes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 27 publications
(36 reference statements)
1
33
0
6
Order By: Relevance
“…This finding is consistent with findings of researchers who recently examined the decision to pursue a postprofessional athletic training program and found the desire to have increased autonomy while receiving mentorship and gaining more advanced knowledge was a priority. 23 According to the literature, anticipatory socialization involves formal educational programs or professional preparation, 7,19,20,27,35,36 whereas organizational socialization occurs when individuals enter into their respective workforces 19,20 and interpret and assume the role of a competent professional. 27,35 Our results demonstrated that by deciding to pursue athletic training, students often chose a route of graduate school with an associated athletic training graduate assistantship.…”
Section: Persist In Athletic Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with findings of researchers who recently examined the decision to pursue a postprofessional athletic training program and found the desire to have increased autonomy while receiving mentorship and gaining more advanced knowledge was a priority. 23 According to the literature, anticipatory socialization involves formal educational programs or professional preparation, 7,19,20,27,35,36 whereas organizational socialization occurs when individuals enter into their respective workforces 19,20 and interpret and assume the role of a competent professional. 27,35 Our results demonstrated that by deciding to pursue athletic training, students often chose a route of graduate school with an associated athletic training graduate assistantship.…”
Section: Persist In Athletic Trainingmentioning
confidence: 99%
“…21 The role of the mentor is pivotal in preparing individuals for their future occupational roles, ensuring that they possess the relevant knowledge and skills to practice. 36 It involves bringing together theory and practice, maintaining and developing an effective learning environment, providing professional support and guidance, enhancing the quality of patient care, progressing the career, and assisting in socializing students into their occupational roles. 36,37 Athletic training students begin to adopt the established perceptions of their mentors 16 ; therefore, when a mentor encourages continued professional development, students are more inclined to follow those recommendations.…”
Section: Persist In Athletic Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The hub mentors were crucial in enabling the spoke practice experience to occur and for the students to gain the maximum benefit from the week. This process reiterated to the mentors the pivotal role that they play in supporting and maximising student learning in practice (Ousey 2009, Jokelainen et al 2011b.…”
Section: Discussionmentioning
confidence: 99%
“…[74] Participants in this study described students who were perceived as overconfident, resistant, or unwilling to learn as not having an ability to "mesh" with the unit's culture. The ability of the student to fit with the group is discussed by Moore et al [69] who say that nurses find that in order to fit, students should be "cheery, outgoing, openminded, friendly, and humble" (p. 176).…”
Section: Discussionmentioning
confidence: 99%